Impact of ICT on Library and Information Services: A Study of AIIMS Insti tutions in Eastern India (LIS TODAY, 2026)
This study examines the integration and effectiveness of Information and Communication Technology (ICT) in library services at AIIMS institutions in Eastern India. AIIMS libraries serve as critical resources for medical education, research, and professional development. The adoption of ICT has transformed traditional library systems, improving accessibility, efficiency, and user engagement through digital repositories, AI-driven search tools, and automated cataloguing systems. Through a mixed-method research approach, this study examines the extent and impact of ICT adoption in AIIMS libraries, focusing on digital resource utilization, user satisfaction, and technological barriers. Surveys and interviews will be conducted among AIIMS library users—including students, researchers, and faculty—to evaluate their experiences with ICT-driven services. Additionally, a comparative analysis of digital infrastructure across AIIMS institutions in Bhubaneswar, Kalyani, Guwahati, Deoghar, and Patna will be undertaken. The research identifies key challenges in ICT implementation, including infrastructure constraints, funding limitations, and user adaptability issues. The findings aim to provide evidence-based recommendations for optimizing AIIMS digital libraries, ensuring seamless access to medical knowledge, and enhancing ICT-driven research capabilities. Moreover, this study offers insights into policy implications, guiding AIIMS institutions toward more effective digital transformations.
Keywords: AIIMS, ICT in Medical Libraries, Digital Knowledge Management, Library Automation, AI-driven Library Systems, E-Resources in Healthcare, Digital Transformation, Services.